2018
DOI: 10.1186/s12906-018-2194-9
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic fermentation augments the skin anti-photoaging properties of Agastache rugosa through up-regulating antioxidant components in UV-B-irradiated HaCaT keratinocytes

Abstract: BackgroundAgastache rugosa (Fisch. & C.A.Mey.) Kuntze (Korean mint) is used to treat diverse types of human disorders in traditional medicine. In recent years, its non-fermented leaf extract (ARE) has been shown to possess protective properties against ultraviolet-B (UV-B) radiation-induced photooxidative stress. The present work aimed to examine whether probiotic bacterial fermentation would potentiate the skin anti-photoaging activity of ARE or not, by comparing the protective properties of ARE and correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 53 publications
1
37
0
1
Order By: Relevance
“…The antioxidant effect of AR was dose-dependent and led to increased HO-1 protein and enzyme activity, and protected cells from H 2 O 2 -induced cytotoxicity [27]. Such response also attenuated UVB-induced photoaging by upregulating anti-oxidant enzymes [28] and reducing the production of ROS [29]. Our results showed that compared with the HFD group, the levels of SOD and GSH in the liver of AR group were significantly increased, while the levels of MDA and ROS were significantly decreased in hepatocytes (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The antioxidant effect of AR was dose-dependent and led to increased HO-1 protein and enzyme activity, and protected cells from H 2 O 2 -induced cytotoxicity [27]. Such response also attenuated UVB-induced photoaging by upregulating anti-oxidant enzymes [28] and reducing the production of ROS [29]. Our results showed that compared with the HFD group, the levels of SOD and GSH in the liver of AR group were significantly increased, while the levels of MDA and ROS were significantly decreased in hepatocytes (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…There are three types of UV radiation as follows: UVA, UVB, and UVC. With regard to the generation of photoaging, UVB is important as it is not only absorbed into the epidermis and the upper part of dermis but also produces more damage to skin than UVA [4,15]. Although UVC is more harmful than UVB, it cannot reach on the surface of earth as it is absorbed by the ozone layer [3].…”
Section: Discussionmentioning
confidence: 99%
“…The architecture of the ECM, conferring elasticity, hydration, and resilience, is closely linked with the features of skin aging. UV, which reaches the surface of the skin and, subsequently, penetrates into the skin, is a harmful damaging external factor causing extrinsic aging or photoaging [4]. Continuous and long-term exposure to UV disrupts the structure of ECM by degrading collagens, remodeling elastic fibers, and aggregating irregular GAG, which in turn, contributes to histological and phenotypic changes consistent with aging including deep wrinkle, skin dehydration, skin thickening, and marked loss of elasticity [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, researchers have used a wide variety of solutions for UV illumination, ranging from home solarium lamps to state-of-the-art solar simulators. By far the most common source of UV light is a lamp with one or more fluorescent tubes [10][11][12][13][14], ranging from simple hand-held lamps [14] or home solariums [10] to UV-crosslinkers [12] and therapeutic illuminators designed for medical use [13]. The second most common type of UV light sources for medical research are solar simulators [15][16][17], which usually employ a high-power Xenon arc lamp with an optical output spectrum very similar to that of natural sunlight.…”
Section: Introductionmentioning
confidence: 99%